Is the Life of the Students of the Northern Region Wealthy, or What the Sociological Survey Data Suggest? - V. P. Zasypkin; G. E. Zborovsky (Высшее образование в России)
The article presents the early results of the sociological research devoted to the wellbeing of the students of Khanty-Mansi Autonomous Okrug – Yugra. The research was held by the staff of Regional researches’ laboratory of Surgut State Pedagogical University in the regional higher educational institutions since February to April of 2022. The assessment of students’ well-being was based upon the analysis of their evaluation, opinions and ideas of it. The novelty of the study lies in the fact that this category is observed in the limelight of presence/absence of the capitals as objective factors and their estimation based upon subjective criteria. The purpose of the article is to identify and analyze the problems of social well-being of students of KhMAO-Yugra based on the study of their assessments, opinions and ideas about it. The objective aspect of students’ well-being is studied through the combination of social, economic, cultural, and symbolic capitals. The subjective aspect is presented as a cognitive and emotional reflection and estimation of objective indicators through the prism of student youth’s opinions. Dissatisfaction with certain aspects of education they get, the desire to drop university, non-priority position of the material factor while choosing a career in favor of an opportunity for self-realization and building a career, etc. was revealed during the process of investigation. The results of the investigation prove the fact of the existence of a number of problems related not only to professional self-identification and professional orientation in students’ environment, revealed in the analysis of the data presented in the article.